Location-allocation models applied to urban public services. Spatial analysis of Primary Health Care Centers in the city of Luján, Argentina - Buzai, Gustavo (Hungarian Geographical Bulletin, 2013)
The actual digital technologies and particularly the association between the Geographical Information Systems (GIS) and the assistance to the Spatial Decision Support System (SDSS) have generated important possibilities for the treatment of spatial information. As regards the use of location-allocation models, this presentation assesses the possibilities of using such models in the field of the geography of services. In this paper theoretical aspects of the analyzed problems are presented, as well as methodological standardized questions for their solution through the use of GIS+SDSS. An applied case study related to the spatial analysis of Primary Health Care Centers (PHCC) in the city of Lujan, Argentina is also presented.